KEANEKARAGAMAN JENIS KUPU-KUPU DI KAWASAN KESATUAN PENGELOLAAN HUTAN (KPH) DESA TIGA BERKAT KECAMATAN LUMAR KABUPATEN BENGKAYANG - Dora, Dora; Indrayani, Yuliati; Dewantara, Iswan (Universitas Tanjungpura, 2019)
Diversity of butterfly species can develop well if in the habitat there are factors that support its population. Protected areas have a higher diversity of butterfly species than those land use conservation area. Beside taking forest product in term of wood or non woody materials, Forest Managemen Unit also provide environmental service such as Clean Water Shelter (PDAM) and Madi Dam. The location of the Madi Dam and Clean Water Shelter are the location that utilized by the communities, this area also have a high diversity of butterfly. The purpose of this study was to obtain data on the diversity of butterflies in the Forest Management Unit in the village of Tiga Berkat lumar sub-district Bengkayang regency. The method used in this research is the transect method. Direct sampling with insect nets is carried out on the transect line. The butterfly found were 28 species with 153 individuals from 4 families are Papilionidae (6 species), Nymphalidae (14 species), Pieridae (6 species) and Lycaenidae (2 species). Diversity index value is 2,98, abundance index value is 0,89, riches index value is 5,36, dominance indexÂ value is 2,14, species similarity index value is 72,72 %.Keywords : Diversity, Butterfly, Forest Management Units